Peran Mediasi Internal Fraud Terhadap Kinerja Perbankan - Riskiyatur Rohemah; Prasetyono; Rita Yuliana (Jurnal Reviu Akuntansi dan Keuangan, 2023)
Purpose: This study aims to determine the direct effect of Good Corporate Governance (GCG) and Risk Management on banking performance, as well as to analyze fraud in mediating the relationship between Good Corporate Governance (GCG) and Risk Management in improving banking performance. Methodology/approach: The method used in this study is a quantitative method using path analysis. The number of samples in this study were 43 conventional banks and 10 Islamic banks. The total sample of 53 banks in the 2016-2020 period is 265 data. Findings: The results of the study show that Good Corporate Governance and Risk Management have an indirect effect on banking performance through fraud. Through this research, the role of GCG and risk management becomes important in improving performance, although not directly. Practical implications: The findings show that although GCG and risk management can improve performance, they have not been able to reduce fraud. So this should be considered properly by the company. Originality/value: The large number of studies on GCG and Risk Management on fraud and performance with inconsistent results indicates that this research can still be explored further. Therefore, this research will fill in the gaps in GCG and risk management research by making fraud a mediating variable.